Needs of informal caregivers of people with a rare disease: a rapid review of the literature - Amy Jayne McKnight; Lynne Lohfeld; Julie Mcmullan (BMJ Open)
Objectives Many people living with a rare disease (RD) are cared for by a family member. Due to a frequent lack of individual RD knowledge from healthcare professionals, the patient and their informal caregiver are frequently obliged to become ‘experts’ in their specific condition. This puts a huge strain on family life and results in caregivers juggling multiple roles in addition to unique caring roles including as advocate, case manager and medical navigator. We conducted a rapid review of literature reporting on the unmet needs of informal caregivers for people living with an RD. All searches were conducted on 14 September 2021, followed by a manual searches of reference lists on 21 September 2021.Setting Searches were conducted in Medline, Embase, Web of Science, GreyLit and OpenGrey.Results Thirty-five papers were included in the final review and data extracted. This rapid review presents several unmet needs identified by informal caregivers of persons with an RD. The related literature was organised thematically: caregiver burden, support through the diagnosis process, social needs, financial needs, psychological needs, information and communication needs and acknowledgement from healthcare professionals.Conclusions This review provides evidence that increased meaningful support is required for caregivers. Active engagement should be encouraged from this cohort in future research and awareness raised of the support available to improve the quality of life for families living with an RD. The unmet needs identified through this review will benefit people living with an RD, caregivers, healthcare professionals and policy makers.